2009
DOI: 10.2223/jped.1947
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, body composition, and food intake of adolescent runway models

Abstract: Objective: To evaluate the bone mineral density (BMD) and to relate it to the food intake and body composition of adolescent runway models.Methods: Cross-sectional study evaluating 33 models and 33 nonmodels aged from 15 to 18 years, paired by age and body mass index (BMI). BMD of spine (L1-L4) was evaluated using the dual-energy X-ray absorptiometry technique (Lunar  DPX Alpha), and body composition was assessed by mean of plethysmography. Food intake was evaluated by a 3-day-food record. Results:The subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
2
0
1
Order By: Relevance
“…To this end, it was verified that the eating standard of Brazilians in relation to dairy products could contribute to a low calcium intake, which was confirmed in the present study, within which it was observed that the greater part of the children and early adolescents presented calcium intake lower than the recommendation. This low ingestion also occurred in other Brazilian studies involving populations of children (43,45) and adults (46,47). On directly analyzing the relation between calcium intake and the z score of bone mineral density of the participants in the present study, no significant correlation was verified, a result similar to that obtained in another study involving Brazilian adolescents with low calcium intake (45).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To this end, it was verified that the eating standard of Brazilians in relation to dairy products could contribute to a low calcium intake, which was confirmed in the present study, within which it was observed that the greater part of the children and early adolescents presented calcium intake lower than the recommendation. This low ingestion also occurred in other Brazilian studies involving populations of children (43,45) and adults (46,47). On directly analyzing the relation between calcium intake and the z score of bone mineral density of the participants in the present study, no significant correlation was verified, a result similar to that obtained in another study involving Brazilian adolescents with low calcium intake (45).…”
Section: Discussionsupporting
confidence: 88%
“…This low ingestion also occurred in other Brazilian studies involving populations of children (43,45) and adults (46,47). On directly analyzing the relation between calcium intake and the z score of bone mineral density of the participants in the present study, no significant correlation was verified, a result similar to that obtained in another study involving Brazilian adolescents with low calcium intake (45). Consequently, studies that evaluate both Brazilian children's and adolescents' bone mass involving different levels of calcium intake are necessary.…”
Section: Discussionsupporting
confidence: 86%
“…Em relação ao mineral cálcio, verificou-se que a ingestão diária dos adolescentes não alcançou as recomendações mínimas em ambas as faixas etárias. Rodrigues et al (2009) relatam que, além da massa corporal, destaca-se, em termos nutricionais, a importante inter-relação entre consumo alimentar e a massa óssea. O período da infância e da adolescência é marcado por uma taxa de formação óssea muito importante, com predomínio da formação sobre a reabsorção (SILVA et al, 2004).…”
Section: Discussionunclassified
“…Consistent with prior research, agespecific and sex-specific z score standardized BMD measures were calculated for use in subsequent analyses. [25][26][27][28][29][30][31] Prescription Medication, Demographic, and Socioeconomic Measures Data on prescription medication was based on responses to the following questionnaire item: "In the past month have you used or taken medication for which a prescription is needed?" followed by the opportunity to list medications.…”
Section: Measures Bmdmentioning
confidence: 99%